Efeitos do redirecionamento de respostas em estereotipias motoras de crianças com autismo - Araujo, Helena de Paula (2025)
Individuals with autism spectrum disorder (ASD) are characterized by communication difficulties that affect social interaction, deficits in socio-emotional reciprocity, and stereotyped interests and behaviors. Stereotypies are repetitive, intense behaviors that occur with high frequency and little variation. There are three types of stereotypies: vocal, motor, and self-directed. When these movements are performed by the child causing physical harm to oneself, they are called self-directed self-harming behaviors. Since such behaviors are incompatible with learning and can lead to social isolation or academic difficulties, the literature has indicated the use of the Response Interruption and Redirection (RIRD) procedure to reduce or eliminate these behaviors. This study aims to investigate the effects of the RIRD procedure on the motor stereotypies of children with ASD. The study employed alternating treatments with RIRD with attention and RIRD without attention. The participants were two children diagnosed with ASD, a 5-year-old girl, and a 6-year-old boy. The results showed a reduction in stereotypies during the intervention phases, which persisted over time in a decreasing curve of response rates. Additionally, the attention variable, as a form of positive reinforcement, did not yield significant differences in the results. These findings support existing literature on vocal stereotypies and replicate the effects of RIRD in reducing stereotypes in children with ASD.